Meta-analysis of complication rates for single-loop versus dual-loop (Roux-en-Y) with isolated pancreaticojejunostomy reconstruction after pancreaticoduodenectomy - Klaiber, Ulla; Probst, Pascal; Knebel, Phillip; Contin, Pietro; Diener, Markus K.; Büchler, Markus W.; Hackert, Thilo (The British journal of surgery, 2015)
Postoperative pancreatic fistula is one of the most important and potentially severe complications after partial pancreaticoduodenectomy. In this context, the reduction of postoperative pancreatic fistula by means of a dual-loop (Roux-en-Y) reconstruction with isolation of the pancreaticojejunostomy from biliary drainage has been evaluated in several studies. This systematic review and meta-analysis summarizes evidence of effectiveness and safety of the isolation of the pancreaticojejunostomy compared with conventional single-loop reconstruction.